Qualificação do acolhimento nos serviços de saúde bucal - Moimaz, Suzely Adas Saliba [UNESP]; Bordin, Danielle; Fadel, Cristina Berger; Santos, Celso Bilynkievycz Dos; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2017)
AbstractIntroduction This study aimed to analyze the quality of care in oral health services regarding its responsiveness to users’ needs.Methodology This cross-sectional and quantitative study included users of the public dental service in the context of Primary Health Care (PHC) in municipalities of three different Brazilian states (n = 1312). Data collection occurred through interviews within health facilities. The study included 15 variables related to the reception process, which were preliminarily analyzed with chi-square tests. The variables associated with the outcome 'responsiveness to users’ needs' were analyzed through logistic regression and feature selection test.Results Negative assessments of full attention to users’ needs were significantly associated with: care provided by the dental surgeon and staff; willingness to discuss doubts, concerns and oral health problems; initial receptivity in the PHC dental service; and provision of information on oral health in the PHC. The other variables were not significantly associated with the outcome variable after the feature selection test.Conclusion the quality of reception in oral health services is significantly related to the humanization of care, responsiveness of dentists and staff and the processes of listening and providing guidance.

ResumoIntrodução Objetivou-se analisar a qualidade do acolhimento no serviço de saúde bucal, considerando sua capacidade de resposta às necessidades do usuário.Metodologia Fizeram parte do estudo transversal, quantitativo, usuários da rede pública odontológica no âmbito da Atenção Primária à Saúde (APS) de três municípios de diferentes estados brasileiros (n = 1.312). A obtenção dos dados deu-se através de entrevista no interior das unidades de saúde. O estudo contemplou 15 variáveis referentes ao processo de acolhimento, as quais foram analisadas preliminarmente com testes qui-quadrado. As que apresentaram associação com a variável desfecho “capacidade de resposta às necessidades do usuário” foram analisadas, posteriormente, por meio da regressão logística e teste de seleção de atributos.Resultados Verificou-se que avaliação negativa do cumprimento das necessidades esteve estatisticamente associada ao atendimento do cirurgião-dentista e equipe; disponibilidade para dialogar sobre dúvidas, preocupações e problemas de saúde bucal; receptividade ao adentrar o serviço odontológico na APS; e recebimento de informações sobre condição de saúde bucal na APS. As demais variáveis não permaneceram associadas de forma significativa após o teste de seleção de atributos.Conclusão A qualidade do acolhimento dos serviços de saúde bucal está significativamente relacionada à humanização do atendimento, receptividade do cirurgião-dentista e equipe e aos processos de escuta e orientação.
Qualification of care in oral health services
Keywords: reception of users; health service evaluation; oral health; acolhimento; avaliação de serviços de saúde; saúde bucal